Simulation analysis of slope stability : a case study on slope failure at new laboratory of Faculty of Mechanical Engineering UTM - Ling, Felix Ngee Leh (2003)
The soil movement on a failed slope had caused substantial failure of sheet pile wall positioned at about 6m from the new laboratory of Faculty of Mechanical Engineering, Universiti Teknologi Malaysia (UTM). To facilitate investigating \,1 causes of the failure, a computer simulation of slope stability using PLAXIS 7.2 is performed to simulate slope conditions before and after construction of the study area. The results of simulation analysis establishes the fact that global soil mass movement started from the elevation of the newly filled water tank to downhill direction toward to installed sheet pile generates a combination of mobilized shear force and lateral pressure larger than the capacity or strength of the sheet pile. The associated stresses also create the occurrence of the up heaving underneath the road pavement adjacent to the new buildings. Furthermore, the simulation analysis deduces that the slope instability becomes greater as moisture or pore-water pressure in the slope increases or decreasing in soil's shear strength.